Combined effects of intense laser field and applied electric field on exciton states in GaAs quantum wells : Transition from the single to double quantum well (2012)
ABSTRACT: The effects of intense laser radiation on the exciton states in GaAs-Ga1–xAlxAs quantum wells are studied with the inclusion of applied dc electric fields oriented along the growth direction of the system. The calculations are made within the effective mass and parabolic band approximations. The intense laser effects have been included along the lines of the Floquet method, modifying the confinement potential associated to the heterostructure. The results for the exciton binding energy, the energy of the exciton-related photoluminescence peak, and the carriers overlap integral are presented for several configurations of the quantum well size, the strength of the applied electric fields, and the incident laser radiation.